2011
DOI: 10.1063/1.3604820
|View full text |Cite
|
Sign up to set email alerts
|

Conformational study of a single molecule of poly para phenylene ethynylenes in dilute solutions

Abstract: The conformation of single molecules of dialkyl poly para phenylene ethynylenes (PPEs), electro-active polymers, is studied in solutions using molecular dynamics simulations. The conformation of conjugated polymers affects their electro-optical properties and therefore is critical to their current and potential uses, though only limited theoretical knowledge is available regarding the factors that control their configuration. The present study investigates the affects of molecular parameters including molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 18 publications
10
22
0
Order By: Relevance
“…The parameters were taken from Refs. [32,33] in which PCFF (polymer consistent force field) force field parameters were converted to OPLS form. Modification for torsional potential parameters of the phenylene rings as evaluated in Ref.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The parameters were taken from Refs. [32,33] in which PCFF (polymer consistent force field) force field parameters were converted to OPLS form. Modification for torsional potential parameters of the phenylene rings as evaluated in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…P θ > 0 describes a co-planar alignment of aromatic rings, while P θ < 0 indicates perpendicular alignments. P θ = 0 and P θ = 1 refer to completely random and fully co-planar alignment of the rings, respectively [32,33]. Figure 3 shows the order parameter versus Δn for 10-PPE with nonyl side chains in toluene and water after 7.7 ns MD simulations in the NpT ensemble.…”
Section: Structural Properties Of Solvated 25-dinonyl-10-ppementioning
confidence: 99%
See 2 more Smart Citations
“…Perahia et al have shown that dinonyl PPE in toluene, at high temperatures and low concentrations form a molecular solution with relatively extended chains while at lower temperatures and higher concentrations, they assemble into aggregates that eventually form a gel. The effect of molecular parameters such as polymer molecular weight and the length of the side chains on PPE conformation in different solvents were studied by Maskey et al They reported that PPE molecules assume extended configuration independent of solvent quality or the nature of the side chains. The relationship between the conjugated polymer conformation and their optical properties such as absorption and emission has been studied by numerous research works, both in solution and in thin films and shown that the chemical structure determines the configuration.…”
Section: Introductionmentioning
confidence: 99%